Asmeniniai įvardžiai ir borealinių kalbų proto-sistemos rekonstravimas (remiantis vakarinių tarmių medžiaga) - Palmaitis, Letas (Baltistica, 1974)
PERSONAL PRONOUNS IN RECONSTRUCTING OF BOREALIC GRAMMATICAL PROTO-SYSTEM If the prime Borealic grammatical structure was an ergative one, it might have been that of Elamite type with non-case means to express relations between subject and object. The article deals with the languages, where traces of the ergative case are distinct. So the appearing of differences between verbals and nomina, as well as the formation of gender and the appearing of conjugation systems are explained as a result of decay of the prime ergative structure. As for pronouns, two lines of them may be tracked out, as personal: 1 p. sg. m∆, 2 p. sg. s∆ (*tu̯- ?), 1 p. sg. nǝ (the first line) and 1 p. sg. H-∆(-G), 2 p. sg. t∆, 1 p. pl. u̯aḥ? (the second line), ∆ marking IE *ǝ, Afro-Asiatic* *a‖ø and ǝ – IE *a, Afr.-А. *ǝ. Such two lines of personal pronouns show, that there were no case flexions in the period of Borealic community, as well as no special markers for plural, while case and number were expressed by different stems. This shows the stem suppletivism of personal pronouns to be a remnant of pre-flexional state. The differentiation between the subject of action and the subject of state in the sphere of pronouns was realized not by joining an ergative marker to the stem, but by using different stems, the ergative marker itself being of pronominal origin. The Borealic “conjugation” had an opposition of paradigms marking state as a process to that marking state as a fact. The first paradigm was formed by joining the first line personal pronouns to the pure stem of the nomen of action while the second one – by joining the second line pronouns. As the subjective markers of the transitive verb are derivable from the personal pronouns of indirect case, the first line personal pronouns must have been ergative stem forms, the second line pronouns being absolute stem forms.